Conceptual Framework of B40 Women’s Entrepreneurial Intention in Malaysia using Theory of Planned Behavior - Peter Marius, Lina Stephanie Winnie; Ambad, Sylvia Nabila Azwa (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Despite Malaysia’s rapid economic growth, a substantial income gap persists, and women-owned businesses remain a minority. The study employs the Theory of Planned Behavior to create a conceptual framework for understanding the factors that influence B40 women’s entrepreneurial intentions. It examines the effect of attitude towards entrepreneurship, family support, and entrepreneurial self-efficacy as crucial drivers of women’s decisions to engage in entrepreneurship. The research methodology will involve using questionnaires that will be distributed to a diverse sample of B40 women in Malaysia. The implications of the study include contributing to Malaysia’s National Entrepreneurship Policy, enhancing support for women entrepreneurs, and motivating more women, particularly those with unstable incomes, to pursue entrepreneurship, thereby fostering greater gender equality and economic development.